Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Rusydan Zakaria; Giantoro Pamungkas; Dewi Adelya; Latifa Khoirunnisa; Gita Cahyani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the effect of profitability, leverage, and company size on company value, focusing on companies listed on the Indonesia Stock Exchange. Using data from 2023, this study applies a quantitative method with multiple linear regression analysis. The results of the analysis show that profitability as measured by Return Of Equity (ROE) has a positive and significant effect on company value, which means that companies with high profitability tend to have better market value. Conversely, leverage as measured by Debt to Equity Ratio (DER) shows varying results; although in some cases it has a positive effect, there are also findings that indicate that leverage does not always increase company value significantly. Company size, as measured by total assets, does not show a significant effect on company value in this context. This indicates that although company size can provide greater access to capital, other factors such as profitability and debt management strategies are more important in increasing company value. This study provides important insights for investors and company managers to understand the key factors that affect company value, and highlights the importance of focusing on profitability and wise debt management in their business strategies.